Identification of Proteins Involved in pH Adaptation in Extremophile Yeast Yarrowia lipolytica - Epova, Ekaterina; Guseva, Marina; Kovalyov, Leonid; Isakova, Elena; Deryabina, Yulia; Belyakova, Alla; Zylkova, Marina; Shevelev, Alexei (IntechOpen, 2012)
None